The use of flexible measures to cope with economic crises in Germany and Brazil - Werner Eichhorst; Paul Marx; José Pastore (Institute for the Study of Labor (IZA), 2011)
This study gives a comparative overview of labor market dynamics and institutional arrangements in Germany and Brazil with particular emphasis on industrial relations, wage setting, unemployment benefits, employment protection and vocational training. The paper shows that institutions determine the mode of adjustment to changing economic conditions and the role of standard vs. non-standard contracts. Whereas internal flexibility via shorter working time was a dominant mode of adjustment during the 2008-09 crisis in the German manufacturing sector, in Brazil such plant-level flexibility to avoid dismissals was less prominent.
urn:nbn:de:101:1-201112136887
Keywords: J21; J42; J52; 330; labor market flexibility; Germany; Brazil; working time; dismissal protection; Arbeitsmarktflexibilität; Arbeitszeitgestaltung; Kündigungsschutz; Wirtschaftskrise; Vergleich; Deutschland; Brasilien